PENGARUH INFLUENCER MARKETING, CITRA MEREK DAN TRUST TERHADAP KEPUTUSAN PEMBELIAN PADA APLIKASI TIKTOK - Primandaru, Noormalita; Marcelino, Bryan; Nasution, Olivia Barcelona (Jurnal Ekonomi Dan Bisnis, 2025)
This study aims to examine the influence of influencer marketing, brand image, and trust on purchasing decisions for the men's skincare brand Elvicto through the TikTok application in Indonesia. A quantitative research method was employed, utilizing a survey of 100 respondents who are TikTok users and have purchased Elvicto products. Data analysis was conducted using validity, reliability, classical assumption tests, multiple linear regression, and hypothesis testing. The results reveal that influencer marketing has a positive and significant effect on purchasing decisions, while brand image and trust do not show a significant impact. This study highlights the crucial role of influencer marketing in shaping consumer purchasing behavior, whereas brand image and trust require further reinforcement to enhance Elvicto’s marketing effectiveness. The novelty of this research lies in its focus on Indonesian male consumer behavior within the TikTok social commerce context, uncovering that influencer marketing exerts a more dominant influence than traditional factors such as brand image and trust, offering a new perspective on digital marketing dynamics in the men's skincare industry.